Extreme programming and its positive affect on software engineering teams - Syed-Abdullah, Sharifah Lailee; Omar, Mazni (2009)
This paper presents an early empirical study on Extreme Programming (XP) practices employing Positive Affect metric.The study was conducted on university students doing development projects to gain an insight understanding of the effect of using agile practices on software engineering (SE) teams.The finding indicates that XP practices do have positive affectivity on the SE teams. This is to be expected because of the existence of the practices such as simple design,pair programming, continuous testing, continuous integration and frequent review (release) that command feedback.This finding helps to provide early empirical evidences on the impact of XP methodology on the positive affectivity of the developers.